A Possible Role for COVID-19 Infection in the Development of Thyroid Disorder - Ali, Maryam; Al-Azzawi, Buthainah (Journal of Biomedicine and Biochemistry, 2022)
Background Coronavirus is the new millennium’s pandemic, with widespread consequences that include pneumonia and systemic contagion, as well as various clinical diagnoses affecting the endocrine system. Objectives To investigate the impact of covid-19 infection on thyroid stability and disease through measuring some biochemical marker that are related to thyroid.• Determine the level of inflammatory marker such as IL-6 and INF- γ Patients & Methods Eighty patients were involved in this case control cohort study all of them attended the isolation wards at Marjan Teaching Hospital in the province of Babylon- Iraq, from September 2021 to February 2022. The group of patients was divided into forty participants were apparently healthy individual without history of any diseases and with negative PCR results. The rest of the participants include: First group forty patients tested positive for Covid-19 infection with no history of thyroid disorder. Following those patients blood sample were collected at different time incident 5th ,10th ,15th and 25 day after diagnosis. Second group after following the patient for 2nd month five of them have symptoms of thyroid disease and after investigation it was confirmed to have thyroid problems. Blood was drawn from the patients for measurement the level of IL-6 and INF- γ concentration using ELISA technique. Results Our analysis of 80 Covid-19 patients and control , it was confirmed IL-6 and INF- γ were significant increase than control group and second. Conclusion In this cohort research of patients infected with Covid-19 infection, both IL-6 and INF- were shown to be significantly higher than in the control and second groups.